Negotiating the Conversation: How Journalists Learn to Interact with Audiences Online. (3rd July 2021) - Martin, Fiona; Murrell, Colleen
ABSTRACT: This paper investigates how young Australian journalists have developed their knowledge of online interaction strategies and how well they feel they manage the challenges of conversations with audiences in comments sections and on social media platforms. It presents the results of a small snowball sample survey and follow-up semi-structured interviews of recent graduates from six universities, working across print, broadcast and social media, exploring their educational preparation and on the job training for dialogic journalism. The survey and interviews build on a literature review that reveals the need for increased research into strategies for dealing with negative responses and speaking to audience diversity. The findings pinpoint areas of journalism pedagogy that need innovation and transformation to address the normalisation of dialogic interaction on social media.